Nitrogen supplementation by leguminous tree leaves for rice (Oryza sativa L.) cultivation - Kumar, Praveen; Das, D.K.; Laik, R.; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
In an attempt to reduce the dose of inorganic N for rice cultivation, the leaves of leguminous tree species were incorporated into soil. The investigation was done at the research farm of Rajendra Agricultural University, Pusa, Bihar. The experimental design was randomized block design with eight treatments and three replications. Leaves of six leguminous tree species namely, Safed Siris [Albizia procera (Roxb.) Benth], Subabul [Leucaena leucocephala (Lam.) de Wit.], Chah (Acacia lenticularis L.), Shisham (Dalbergia sissoo Roxb.), Karanj [Pongamia pinnata (L.) Pierre] and Chakundi (Cassia siamia Lamk.) were applied @ 5 ton ha-1 along with half dose of nitrogen and full dose of P and K. The treatments were compared with the plots receiving full dose of N, P and K and with control. L. leucocephala treated plots showed maximum grain yield (44.28 q ha-1) which was at par with plots receiving A. procera leaves. These two treatments along with P. pinnata leaf applied plots had significantly more grain yield than that of the plots which was applied with recommended doses of N, P and K. D. sissoo treated plots had the lowest grain and straw yield and N uptake, among the leaf treated plots and the plots with fertilizer 100% NPK. Yield attributing characters like height of plant, panicle length, number of grains per panicle and thousand grain weights were also maximum in L. leucocephala incorporated plots. Incorporation of leaves of A. procera and P. pinnata could increase thousand grain weights over the absolute chemical fertilizer treated plot. Hence green manuring with the leaves of L. leucocephala, A. procera and P. pinnata at 5 ton ha-1 can save half of the dose of inorganic N for rice cultivation.